2020
DOI: 10.32598/ijmtfm.v10i3.30051
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Chronological Age by Dental Measurements on the Periapical Radiographs in Iranian Adults

Abstract: Objectives: This study aimed to assess the accuracy of chronological age estimation based on dental measurements made on periapical (PA) radiographs of an Iranian adult population. Materials and Methods: This study evaluated 90 parallel PA radiographs of sound maxillary canine teeth of 39 males and 51 females. Tooth length, root length, pulp length, pulp width and root width at points A, B and C according to the Kvaal’s method were measured on PA radiographs using Scanora software. Data were analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Anterior and lateral neck hemorrhages in nonasphyxial, nontraumatic deaths are relatively common. 18 Such hemorrhages deserve special attention, for they may be mistakenly attributed to neck compression. Caution must be used when anterior neck lividity is encountered at autopsy to ensure accurate etiological attribution and diagnoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anterior and lateral neck hemorrhages in nonasphyxial, nontraumatic deaths are relatively common. 18 Such hemorrhages deserve special attention, for they may be mistakenly attributed to neck compression. Caution must be used when anterior neck lividity is encountered at autopsy to ensure accurate etiological attribution and diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior and lateral neck hemorrhages in nonasphyxial, nontraumatic deaths are relatively common 18 . Such hemorrhages deserve special attention, for they may be mistakenly attributed to neck compression.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common methods of attempted suicide worldwide is by hanging. As such, Akhlaghi et al [ 14 ] reported that 22.1% of the attempted suicides were done by hanging. Also, 75.4% of all attempted suicides were done by hanging in Ilam city [ 15 ].…”
Section: Discussionmentioning
confidence: 99%